Characterization of insect cytosolic juvenile hormone binding protein gene: Highly homology with vertebrate glyoxalase domain containing protein 4. (February 2015) - Li, Yan; Peng, Minghui; Chen, Miaomiao; Li, Yuping; Zhang, Qirui; Jiang, Xingfu; Liu, Yanqun
Abstract: Cytosolic juvenile hormone binding protein (cJHBP) is a carrier of juvenile hormone (JH) in insects, however knowledge about its evolution and expression remains extremely limited. In this study, a gene encoding for cJHBP was isolated from the Chinese oak silkmoth Antheraea pernyi . A database search showed that the homologous sequences were present in several animal species including nematodes, insects, tunicates, fish, and mammals. The A. pernyi cJHBP had 54–85% identity with its homolog from other insects, and 58–62% identity with vertebrate glyoxalase domain containing protein 4 (Glod-4). Phylogenetic analysis supported the hypothesis that insect cJHBP shares a common ancestor with vertebrate Glod-4. RT-PCR detection showed that the cJHBP gene was expressed throughout the developmental stages and in all tested tissues of A. pernyi, which agreed with the data from Bombyx mori cJHBP and Homo sapiens Glod-4 . These data suggest that insect cJHBP may play a similar function as vertebrate Glod-4. Graphical abstract: Highlights: We investigate the expression pattern of the cJHBP gene in A. pernyi . We evidence that insect cJHBP shares a common ancestor with vertebrate Glod-4. We link insect cJHBP with vertebrate Glod-4.